2008
DOI: 10.3324/haematol.11828
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine-melphalan as a preparative regimen for reduced-intensity conditioning allogeneic stem cell transplantation in relapsed and refractory Hodgkin's lymphoma: the updated M.D. Anderson Cancer Center experience

Abstract: BackgroundThe role of reduced-intensity conditioning allogeneic stem cell transplantation in relapsed/refractory Hodgkin's lymphoma remains poorly defined. We here present an update of our single-center experience with fludarabine-melphalan as a preparative regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
117
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 34 publications
6
117
1
1
Order By: Relevance
“…3 Furthermore, Anderlini et al recently reported a 2-year PFS rate of 57% in patients who achieved CR/CRu before alloSCT using a similar RIC regimen without alemtuzumab. 2 However, none of those reports described a correlation between FDG-PET findings and outcome.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3 Furthermore, Anderlini et al recently reported a 2-year PFS rate of 57% in patients who achieved CR/CRu before alloSCT using a similar RIC regimen without alemtuzumab. 2 However, none of those reports described a correlation between FDG-PET findings and outcome.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] RIC regimens also have been investigated in patients with aggressive lymphomas: Most of those studies included various B-cell and T-cell histotypes, and the estimated 3-year PFS rates have been 15% to 20% in patients with chemoresistant disease and 45% to 55% in patients with chemosensitive disease. [4][5][6][7] Chemosensitivity is 1 of the most important prognostic factors affecting final outcomes in patients who receive myeloablative conditioning, and is also important for patients who receive RIC regimens.…”
mentioning
confidence: 99%
“…[65][66][67] Peggs et al 65 reported on 49 patients (90% failed prior auto-HCT) who received conditioning with fludarabine, melphalan and alemtuzumab prior to allo-HCT. Donor source consisted of MRD in 31 and URD in 18 patients.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…The first 14 patients received conditioning with fludarabine and CY with or without antithymocyte globulin. 67 Because of early progression, the subsequent 26 patients received fludarabine plus melphalan. 67 Use of melphalan resulted in a higher OS rate at 18 months (73 vs 39%, P ¼ 0.03) and lower NRM (18 vs 30%).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation